قحط سالی اور دیگر قدرتی آفات: تدارک اور عملی اقدامات (اسوۂ حسنہؐ کی روشنی میں): Famines and Natural Disasters: Termination and Practical Steps in the Light of Sirat Al-Nabi (SAW) - Dr. Abdul Ghaffar, (Seerat Studies, 2023)
Pakistan is under the cloud of famines and natural disasters. Specially, most of the regions of Baluchistan and Sindh are under this stress. Land is barren now and due to shortage of water and grass animals and masses are dying. Due to the load shedding daily routine of life is almost struck. Due to lack of food and environmental pollution people are facing numerous diseases. There is dire need to discover real causes for all these problems. When the Holy Prophet (PBUH) laid down the foundation stone of Madina as an Islamic State, such problems were rampant. The lack of food, over population and issues of immigrants were common. The Prophet (PBUH) settled all these issues for the welfare of society with strong and outstanding planning. As a result, in few years Madina Munawra emerged on the map of the world as a perfect developed state. In this article different suggestions for making Pakistan such a developed country by keeping in mind those practical implications and planning adopted by the mercy for mankind, Muhammad (S.A.W).